Generation of typical meteorological year (TMY-2) for Nicosia, Cyprus - Kalogirou, Soteris A. (My University, 2003)
The present paper presents the generation of a type 2 Typical Meteorological Year (TMY-2) for Nicosia, Cyprus. This tool may be useful for the prediction and comparison of the performance of passive and active solar systems and for building thermal analysis. The present TMY-2 is generated from a simple TMY created in the past from available hourly meteorological data recorded during the period 1986–1992 using the Filkenstein–Schafer statistical method. The present TMY-2 contains much more data which leads to more accurate predictions especially in building simulations. This includes in addition to solar radiation values, illuminance, and other meteorological elements such as visibility, precipitation and snowfall records.
Keywords: TMY